2021
DOI: 10.3390/toxins13050302
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulant Activity of Naja nigricollis Venom Is Mediated by Phospholipase A2 Toxins and Inhibited by Varespladib

Abstract: Bites from elapid snakes typically result in neurotoxic symptoms in snakebite victims. Neurotoxins are, therefore, often the focus of research relating to understanding the pathogenesis of elapid bites. However, recent evidence suggests that some elapid snake venoms contain anticoagulant toxins which may help neurotoxic components spread more rapidly. This study examines the effects of venom from the West African black-necked spitting cobra (Naja nigricollis) on blood coagulation and identifies potential coagu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 60 publications
1
14
0
Order By: Relevance
“…This study is congruent with prior work, demonstrating the efficacy of varespladib against a wide range of snake venom PLA 2 -driven pathophysiological actions (20,26,30,(32)(33)(34)(43)(44)(45)(46)(47)(48), thereby underscoring the potential utility of this compound as a first-aid option. For instance, field treatment options such as varespladib could stabilize patients in remote locations while being transported to hospital, and or serve as the only treatment option for some snake species such as the potent FXa-inhibiting anticoagulant effect of the African spitting cobra venoms included in this study (18,24,26,(49)(50)(51).…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…This study is congruent with prior work, demonstrating the efficacy of varespladib against a wide range of snake venom PLA 2 -driven pathophysiological actions (20,26,30,(32)(33)(34)(43)(44)(45)(46)(47)(48), thereby underscoring the potential utility of this compound as a first-aid option. For instance, field treatment options such as varespladib could stabilize patients in remote locations while being transported to hospital, and or serve as the only treatment option for some snake species such as the potent FXa-inhibiting anticoagulant effect of the African spitting cobra venoms included in this study (18,24,26,(49)(50)(51).…”
Section: Resultssupporting
confidence: 88%
“…We also ascertained the ability of prinomastat to cross-react with the anticoagulant PLA 2 of these medically important snakes. In addition to undertaking the first anticoagulant toxicity testing for N. ashei, N. katiensis, and N. nubiae venoms, this work builds upon increasingly popular research into non-immunoglobulin treatments for snakebites using temperature-stable small molecule inhibitors (SMIs) that may improve snakebite firstaid in remote areas (20,26,(30)(31)(32)(33)(34). Therefore, our results hopefully inform and streamline future platform testing while minimizing the need for in vivo animal testing.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…A previous study observed a much clearer negative anticoagulant peak with D. typus venom, though the venom was applied at a five-fold higher concentration (5.0 mg/mL venom) than that used in this study (1.0 mg/mL venom) 29 . While varespladib has previously been demonstrated to be a potent inhibitor of anticoagulant venom activities induced by PLA2 toxins 33,[40][41][42] , in this study it produced no inhibitory effects on venom-induced coagulation, whether procoagulant or anticoagulant, at the maximal drug dose tested (20 μM) (Supplemental File S2). However, due to the weak anticoagulant venom activity observed in these experiments, the assay window for measuring such inhibition is limited.…”
Section: Inhibitory Effects Of Small Molecule Drugs On Nanofractionated D Typus Venom Coagulotoxinsmentioning
confidence: 62%